Rights of Nature in Action: An Analysis of Laws in Ecuador - Wuraola, Oluwabusayo (Ecuadorian Science Journal, 2025)
Background: The growing global interest in the rights of nature goes beyond simply granting legal rights to trees, rivers, oceans, and other natural entities. A key question arises: how can these ecosystems be represented in courts as legal persons capable of defending their own interests? Objective: This article examines how the legal framework in Ecuador recognizes the rights of nature and evaluates the mechanisms through which ecosystems are represented in court. It proposes an eco-centric representation model that ensures effective and justiciable protection of these rights. Methods: A doctrinal legal analysis was conducted using Ecuador’s 2008 Constitution as the primary legal framework. The study draws on case law, academic literature, legislation, and international legal perspectives to assess how representation is currently operationalized in Ecuador. Results: The review reveals that, although Ecuador has taken a pioneering role by constitutionalizing the rights of nature, gaps persist in the legal mechanisms for representation. Judicial cases show inconsistent application of these rights, often dependent on anthropocentric interpretations and the capacities of human representatives. Conclusion: To strengthen the enforceability of the rights of nature, the legal framework in Ecuador should be revised to provide clearer guidelines for representation. Additionally, representatives must be trained to embody eco-centric values, ensuring authentic and effective advocacy for ecosystems as legal persons.